Hybrid Contact Lenses in Children: a Case Series: Poster Presentation - Case Series - Ophthalmologist - ADISTI LUKMAN (Majalah Oftalmologi Indonesia, 2023)
Introduction : Refractive errors in children have experienced a significant increase in recent years. Contact lenses are a therapeutic option when spectacles can no longer provide maximum results. One of the most advanced design than suitable for children is Hybrid Contact Lenses (HCL). HCL feature a Rigid Gas Permeable (RGP) center surrounded by a soft ridge or skirt. This design enable the hard center to provide clear vision while the soft skirt offers the comfort and ease of a soft lens. However, this type of contact lens has not been widely used in Indonesia. Case Illustration : Three patients were prescribed HCL to correct their high refractive errors and amblyopia; 1. 5 years old female: OD: S-14.50 C-3.25x180 6/24 OS: S-12.5 C-3.50x10 6/24; 2. 5 years old female with anisometropia: OD: S-6.00 C-2.50x180 6/12 OS: S-0.75 C-2.000x170 6/6; 3. 8 years old male with pseudophakic eyes: OD: S-9.00 C-2.00x180 6/30 OS: S-8.00 C-2.00x175 6/30. Visual Acuity after 1 month of HCL average from 6/9 to 6/6 both eyes (BE). Discussion : In this study, we can notice several advantages of using HCL. The main outcome are significantly increased visual acuity and reduced amblyopia. HCL also has a higher comfort level compare to RGP Lenses, the soft hydrogel skirt really help the neophyte patient to ease their initial adaptation. Conclusion : Contact lenses are a mainstay of optical correction options for children with special refractive needs. Due to it's design and comfort, HCL is one of the most suitable contact lenses for children. Therefore, socialization and further introduction about this contact lens is needed.